Incident Potential Index Model Complimenting Malaysia Disaster Management Environment - S, Khairilmizal; F Hussin, M; Ihsan Mohd Yassin, Ahmad; Khairul Mohd Salleh, Mohd; Husna K., Ainul; Huzaimy Jusoh, Mohamad; Asari Sulaiman, Ahmad; Saadun, Jamil; Haikal Kasri, Mohd; R Hussain, A (International Journal of Engineering and Technology, 2018)
Disaster management is a process cycle of disaster prevention, preparedness, response, and recovery. The revised Malaysia disaster management policy, MNSC 20 was published in compliance with international disaster management frameworks. Unfortunately, MNSC 20 did not elucidate stages before the district level of disaster hence, a model of an incident potential index needs to be developed and defined. By utilizing content validity method in analysing MNSC 20, lead responding agency documentation and several disaster management plans developed and endorsed by the lead responding agency, a model of Incident Potential Index Complimenting MNSC 20 was introduced. The model shows that there were three (3) Tiers needed to be considered by community members before the activation of MNSC 20. This model is considered effective as its seemingly dovetails the response and recovery efforts of the community members with the lead responding agency in Malaysia. By implementing the model, it is believed that community disaster plan, including the oil and gas industry, can be standardized in defining levels of disasters which indirectly compliment the MNSC 20 when activated.Â Â